Identification of bioactive factors from Abrus precatorius by GC–MS, NMR and evaluation of its antioxidant activity. (2020) - Pavithra, K.; Uddandrao, V.V. Sathibabu; Mathavan, S.; Gobeeswaran, N.; Vadivukkarasi, S.; Ganapathy, Saravanan
Abstract: The current study was designed to develop fingerprint of the different bioactive compounds of Abrus precatorius and evaluation of its antioxidant activity. C-13 and H-NMR analysis of A. precatorius elucidated the key bioactive compounds in the leaves that were consistent with the classes of bioactive compounds detected by GC–MS analysis which revealed the presence of 9 major compounds. A. precatorius shown significant free radical scavenging activities and contain antioxidative enzymes which can regulate the free radical activity. In conclusion, the present study identified an array of bioactive compounds present in A. precatorius and reported their ethno-botanical uses against free radicals.